EXPLORING THE IMPACT OF PROJECT-BASED LEARNING IN MANDARIN LANGUAGE EDUCATION: A CASE STUDY - Mutmainnah D, Muthia; Utami R, Winda Ayu; Kadar, Annisa Syauqina (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research explores the transformative potential of Project-Based Learning (PBL) in Mandarin language education by presenting a comprehensive case study. Highlighting the increasing importance of Mandarin proficiency in today's education world, the study investigates how PBL fosters language skills and cultural understanding. Drawing upon a mixed-methods research design, the study assesses pre- and post-implementation outcomes, student engagement, linguistic competence, and challenges faced in PBL adoption. Findings indicate that PBL enhances student engagement, motivation, and linguistic proficiency, while also deepening cultural understanding. Despite challenges in implementation and assessment, the study advocates for the integration of PBL in Mandarin instruction to create dynamic and immersive learning environments that prepare students for success in a globalized world.